Một vài kết quả về các ràng buộc trên các giá trị không trong CSDL quan hệ - Tuan, Tran Doan (Journal of Computer Science and Cybernetics, 2018)
In [2] B.S. Goldstein introduced the concept of “disjunctive existence constraint” together with a sound and complete set of inference rules (4 rules), as a means for using null values. In this paper, we investigate cases in which the system of three inference rules is complete. Finally, an algorithm for computing the closure X* of X is also given.